Evaluation of the level of service of vehicular flows in case signalized intersections two: Alto de la Alianza - Tacna. - Maquera Cruz, Pedro Valerio (2020)
This thesis analyzes the problem of the congestion of the current vehicular flow, made up of public and private vehicles, passenger and cargo vehicles, light and heavy vehicles, existing at Av. Jorge Basadre Grohmann intersection with Av. Tarata and Av. Internacional. The study evaluates the vehicular flows in periods of 15 minutes to obtain the vehicular flow in rush hour, for that reason the objective of the present thesis was to evaluate the service level of the vehicular flows in the proposed intersection, due to the generated congestion by the flow, the traffic and the quality of the road. The semaphore of the intersection Av. J. Basadre with Av. Tarata, has three phases adding a cycle of 76 seconds between green, amber and red, while the traffic light of Av. J. Basadre with Av. Internacional, has two phases adding a cycle of 76 seconds, these two intersections have a synchronization in the green phase for Av. J. Basadre from East to West. In relation to the number of lanes, the Jorege Basadre Avenue has three lanes in each direction, the Tarata Avenue has one in each direction and two in each direction, and the Av. Internacional has two lanes in each direction, the state of the roadway is regular. to bad. To know the level of service, the HCM 2010 analysis methodology and the Synchro V8.0 program have been applied, the simulation of the vehicular flow has resulted in an "F" level of service, and some results have been proposed for this result. solution alternatives to improve service level of the vehicular flow at said intersection, such as the optimization of cycle times and change of phases of traffic lights, another alternative is to generate a road exchange considering the two intersections to have free flows of saturation.